Endophytes and their potential in biotic stress management and crop production - Chaudhary, Parul; Agri, Upasana; Chaudhary, Anuj; Kumar, Ashish; Kumar, Govind (Frontiers in Microbiology, 2022)
Biotic stress is an adverse condition and caused by harmful microbes that prevents plants from growing normally and causes numerous negative effects on agricultural crops globally. Many biotic factors such as bacteria, fungi, virus, weeds, insects and nematodes are the major constrains of stress that tends to increase the reactive oxygen species which affect the physiological and molecular functioning of plants and also led to decrease in crop productivity. It is essential to develop novel control strategies towards the plant pathogens and biotic stress management. Bacterial and fungal endophytes are the solution to overcome the tasks faced with conventional farming these are environment friendly microbial commodities which colonize in plant tissues without causing any damage. Endophytes play an important role in host fitness, uptake of nutrients, synthesis of phytohormone and diminish the injury triggered by pathogens via antibiosis, production of lytic enzymes, secondary metabolites, and hormone activation. They are also reported to help plants in coping with biotic stress, improving crops and soil health, respectively. Therefore, usage of endophytes as biofertilizers and biocontrol agent have developed an eco-friendly substitute for destructive chemicals for plant development and also in mitigation of biotic stress. Thus, this review highlighted the potential role of endophytes as biofertilizers, biocontrol agent and in mitigation of biotic stress for maintenance of plant development and soil health for sustainable agriculture.